Development of the first geldanamycin-based HSP90 degraders - Wurnig, Silas; Vogt, Melina; Hogenkamp, Julian; Dienstbier, Niklas; Borkhardt, Arndt; Bhatia, Sanil; Hansen, Finn K. (Frontiers in Chemistry, 2023)
Despite the early clinical promise, adverse events such as acquired resistance and dose-limiting toxicities have barred the widespread use of HSP90 inhibitors as anticancer drugs. A new approach involving proteolysis-targeting chimeras (PROTACs) to degrade the protein instead of inhibiting it may overcome these problems. In this work, we describe the design, synthesis, and evaluation of cereblon-recruiting geldanamycin-based HSP90 degraders based on the PROTAC technology. Our best degrader, 3a, effectively decreased HSP90α and HSP90β levels in cells utilizing the ubiquitin–proteasome pathway.